Antioxidant Activity of Extract from Ultrasonic-Assisted Extraction of Durian Peels - Bambang Kunarto; Ely Yuniarti Sani (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2018)
The increase in durian production results in the accumulation of durian peel waste. The bioactive component of durian peel has the potential to be used as an antioxidant. Thus, there is a need to carry out an extraction process to obtain bioactive compounds from durian peel. However, conventional extraction methods cause damage to phenolic compounds due to oxidation, hydrolysis and ionization reactions during the extraction process. Therefore, durian peel extraction was carried out using ultrasonic assisted extraction method (UAE) in this study. The purpose of this study was to investigate the effect of varying ratios of durian peel to ethanol solvents and extraction time on the yield, total phenolics content, total flavonoids content and antioxidant activity. The results of the research data were analyzed using a two-factor completely randomized design, which included variations of the ratio of durian peel to ethanol solvents and extraction time The Duncan’s New Multiple Range Test (DNMRT) was carried out as a follow up test to determine the differences in each treatment at a significance level of 0.05. The results showed that the best treatment for peel extraction using ultrasonic assisted extraction was a 1: 9 ratio of durian peel to ethanol at an extraction time of 20 minutes. The extraction of durian peel under this condition gave the highest yield of 12.77 ± 0.16%, antioxidant activity (IC50) of 38.33 ± 0.12 ppm, total phenolic content of 63.30 ± 0.08 mgGAE / g and total flavonoids content of 47.53 ± 0.48 mgQE / g. In addition, total phenolics content and total flavonoid content showed a strong correlation to the antioxidant activity of durian peel extract.